TWO NEW SPECIES OF PARATYLENCHIDAE FROM MANIPUR - MOHILAL, N.; DHANACHLAND, CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Two species of nematodes that are found to be new to science are reported herein. They are Paratylenchus canchicus n.sp. and Graciacus anchora n.sp. On comparison with other related species Paratylenchus canchicus is found to be closer to P. nanus Cobb. 1923 but differentiating from it in the position of the excretory pore, length of stylet, prorhabdion and in the shape of the tail. Graciliacus anchora comes close to G. costata Raski, 1976 but differs markedly in its size, anchor shaped stylet knob, slightly curved body, short isthmus, non-protuded vulvallips and position of excretory pore.